Public Policies for the Promotion of Horticulture: The Case of Algarve's Citrus - Emilia Madeira; Jo\~ao Guerreiro; Agostinho Carvalho (European Regional Science Association (ERSA), 2010)
This research approaches same factors that have been affecting the competitiveness faced by the Algarve citrus culture since the European Single Market came into force and before a more and more global economy. According to the conceptual and theoretical framework, in a global economy any competitive strategy must have underlying quality(ies).These understood as the capacity to satisfy the market considered as a whole of the main types of agents at the different levels of Algarve citrus system. So, the main object of this work is to identify eventual (technical and institutional) malfunctions concerning the Algarve citrus system, that can fail either directly or indirectly to meet the principal clients/consumers'expectations. The study focus on the analysis of the general context where the Algarve citrus culture is inserted, under the socio-cultural, political-legal and economic point of view. The aim is to identify the constraints faced by the sector in order to understand the main clients, suppliers and competitors behaviours, being this part what we consider as the present thesis core. The results have allowed us to characterize the quality attributes considered as determinants when citrus are acquired, namely the Algarve citrus, by the national consumers as well as by the main distribution channels, in case they are presented in the market as differentiated or undifferentiated. The facts identified in the empirical research indicate that limitations of technical and institutional order can make unfeasible or strongly condition the capacity of the Algarve citrus culture (production subsystem, the chain's first link) to meet the market requirements. The conclusions reached for the development of the Algarve citrus culture, were based on Hayami and Ruttan's "induced technical and institutional innovation" theory (1998). We think we have given a contribution towards the definition of strategies for the Algarve citrus culture development, bearing in mind both the market and the available resources.
Keywords: 330; competitiveness; strategy; quality(ies); IGP - "Algarve's Citrus"; technical and institutional innovation; citrus system